Green Scandal Implementation on Corporate Social Responsibility Reporting: A Systematic Literature Review - Mediaty; Indo Sengngeng; Abdul Hamid Habbe (International Journal of Business and Applied Economics, 2023)
This research aims to analyze and examine empirical evidence regarding corporate green scandals in the disclosure of Corporate Social Responsibility. Using the Systematic Literature Review method by taking previous research data. Researchers selected samples from several literature that had been obtained through Simplified Approach analysis in order to simplify each finding. Thus, 30 articles were obtained that were considered relevant in this research to answer the research questions that had been formulated. From the research, it was found that CSR disclosures carried out by companies are a form of legitimacy and are expected to provide the view that organizations are continuously trying to create harmony between the social values inherent in a company's activities and the behavioral norms that exist in the social system of society. CSR implementation should be an initial investment because it can provide long-term benefits to the company.